2010
DOI: 10.1111/j.1432-2277.2010.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia-inducible VEGF gene expression on revascularization and graft function in mouse islet transplantation

Abstract: Summary For gene transfer strategies to improve islet engraftment, vascular endothelial growth factor (VEGF) expression should be regulated in a way that matches the transient nature of revascularization with simultaneously avoiding undesirable effects of overexpression. The aim of this study was to investigate the effects of hypoxia‐inducible VEGF gene transfer using the RTP801 promoter on islet grafts. We implanted pSV‐hVEGF transfected, pRTP801‐hVEGF transfected or nontransfected mouse islets under the kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It has been reported that administration of GH increases proliferation of β cells in transplanted islets (49). Nerve growth factor (NGF) and VEGFs play a critical role in development of β cells and are also associated with the survival of islets in vivo following transplantation (50)(51)(52). GHRH(1-29)NH 2 was reported to stimulate the expression of VEGF in vitro (53), and, correspondingly, GHRH antagonists strongly inhibited the expression of VEGF in tumor (54).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that administration of GH increases proliferation of β cells in transplanted islets (49). Nerve growth factor (NGF) and VEGFs play a critical role in development of β cells and are also associated with the survival of islets in vivo following transplantation (50)(51)(52). GHRH(1-29)NH 2 was reported to stimulate the expression of VEGF in vitro (53), and, correspondingly, GHRH antagonists strongly inhibited the expression of VEGF in tumor (54).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 α is transcriptional factor involved in VEGF expression and regulates the development of MDSC [89]. In transplantation, hypoxia-induced VEGF enhances engraftment and prolongs islet allograft survival [90, 91]. Anti-VEGF treatment has shown promising results in tumor-bearing mice by reducing MDSC accumulation and preventing T-cell anergy and Treg development [92].…”
Section: Mdsc Development and Therapeutic Applicationsmentioning
confidence: 99%
“…Insulin staining, TUNEL method and H&E staining were performed using the same procedure as above. Specimens were stained by immunohistochemistry for VEGF for vascularization 50,51 and HIF-1a to determine hypoxia. 11,12 Primary antibodies were goat anti-VEGF antibody (Santa Cruz Biotechnology Inc., sc-1836) diluted 1:50, and goat anti-HIF-1a antibody (Santa Cruz Biotechnology Inc., sc-12542) diluted 1:25.…”
mentioning
confidence: 99%